Dari Studio ke Layar: Efektivitas Berbagai Perangkat Pembelajaran Tari Berdasarkan Penelitian - Mesy Nadia Safitri; Mega Kencana; Suci Fajrina (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
In today's digital era, the dance learning process is no longer limited to conventional studios. Various technologies, ranging from instructional videos and interactive media to virtual reality, are increasingly being utilized in dance education. Through a systematic literature review (SLR), this study examines the effectiveness of various dance learning tools based on empirical findings and development studies. This study compiles, compares, and summarizes research findings on the use of various media (such as video, VR, interactive PowerPoint, and augmented reality) and their impact on several aspects, including material comprehension, movement skills, aesthetic appreciation, and student engagement. The analysis shows that digital technology can improve dance learning outcomes across the cognitive, psychomotor, and motivational domains. However, challenges such as limited technological facilities and the need for teacher training still need to be addressed. This study also provides recommendations for educators and dance learning developers to integrate technology in harmony with appropriate pedagogical approaches.